Applying software process modeling to improve customer support processes. Issue 4 (14th April 2015) - Raninen, Anu; Merikoski, Helena; Ahonen, Jarmo J.; Beecham, Sarah
Abstract The quality of an organization's support services can be key to maintaining and extending its customer base and to its future survival. As such, support services need to be considered in software process improvement initiatives and not left as an afterthought or stand‐alone effort. However, to identify areas in need of improvement requires a good understanding of the current process. To meet this need, we have developed a process modeling technique called LAPPI that documents current 'as‐is' processes. This study explores whether the LAPPI can identify opportunities for improvement in the customer service process. LAPPI is applied, step by step, in a small‐to‐medium‐sized enterprise. Results are validated through an analysis of customer satisfaction questionnaires administered before and after our LAPPI intervention. Applying the LAPPI highlighted several problems with the customer support service, which was subsequently streamlined. The validation shows an improvement in customer satisfaction in several areas, with significant improvement in customer response times and in customer query resolution. Software development organizations can use LAPPI to highlight where improvements are needed in support services. This study shows that making best use of support resources and ensuring customers receive prompt and clear help throughout the product's lifetime can improve an organization's image and future prosperity. Copyright © 2015 John Wiley & Sons, Ltd.